Cellular Responses to Membrane and Nucleocapsid Viral Proteins Are Also Boosted After SARS-CoV-2 Spike mRNA Vaccination in Individuals With Either Past Infection or Cross-Reactivity - Vallejo, Alejandro; Martín-Hondarza, Adrián; Gómez, Sandra; Velasco, Héctor; Vizcarra, Pilar; Haemmerle, Johannes; Casado, José L. (Frontiers in Microbiology, 2022)
SARS-CoV-2 spike mRNA vaccines have shown remarkable clinical efficacy in the general population, although the nature of T cell priming is not fully understood. We performed longitudinal spike-, membrane- and nucleocapsid-specific T cell analysis in individuals with past infection and infection-naïve individuals with cross-reactivity. We found an additional enhancement of T-cell response to structural membrane (M) and nucleocapsid (N) SARS-CoV-2 proteins after mRNA vaccine in these individuals. Thus, despite the spike-specific response, we found that the first dose of the vaccine elicited a significant CD8 cell response to M and N proteins, whereas no cellular response to those proteins was found in infection-naïve individuals without pre-existing cross-reactivity who were tested for eventual asymptomatic infection. These findings highlight the additional benefit of mRNA vaccines as broad boosters of cellular responses to different viral epitopes in these individuals, and suggest an extended protection to other viral variants.